Healthcare and welfare policy efficiency in 34 developing countries in Asia - Kim, Yong Chan; Park, Min Jae; Atukeren, Erdal (International Journal of Environmental Research and Public Health, 2020)
The healthcare and welfare policies of nations, as well as the amount of investments put into these areas, vary across countries. Investments in healthcare and welfare have been increasing worldwide which brings the question of assessing the efficiency of these investments. There are, however, difficulties in evaluating the effectiveness of such investments due to differences in countries’ economic development levels and due to the differences in data definition issues. There are only a limited number of studies in the literature that employ consistent and comparable indicators across countries. This study evaluates the healthcare investment efficiency and health competitiveness efficiency of 34 developing countries in Asia using a two-stage dynamic data envelopment analysis approach. Furthermore, we employ a broader measure of indicators on national healthcare and welfare policies and outcomes, in addition to the investment data on healthcare and welfare expenditures. Our findings indicate that the establishment of an investment environment with a consolidated approach and management is an important factor that increases the efficiency of investments in healthcare and welfare sectors. A consistent delivery of the national policy strategy is also crucial for reaching the medium-and long-term targets for each country. For example, if a country establishes healthcare and welfare policies that focus on improving its indicators with low efficiencies, the output will be improved and a better return on investment will be ensured in a long-term perspective.
Keywords: Asia; Delivery of Health Care; Developing Countries; Economics; Efficiency; Female; Health Policy; Humans; Investments; Population Dynamics; Pregnancy; Asian economies; Data envelopment analysis; Economic development; Efficiency of investments; Health economics; Healthcare investments; Healthcare policy; Human capital